Nanostructured Lipid Carriers to Mediate Brain Delivery of Temazepam: Design and In Vivo Study - Nermin E. Eleraky; Mahmoud M. Omar; Hemat A. Mahmoud; Heba A. Abou-Taleb (MDPI AG, 2020)
The opposing effect of the blood-brain barrier against the delivery of most drugs warrants the need for an efficient brain targeted drug delivery system for the successful management of neurological disorders. Temazepam-loaded nanostructured lipid carriers (NLCs) have shown possibilities for enhancing bioavailability and brain targeting affinity after oral administration. This study aimed to investigate these properties for insomnia treatment. Temazepam-NLCs were prepared by the solvent injection method and optimized using a 42 full factorial design. The optimum formulation (NLC-1) consisted of; Compritol® 888 ATO (75 mg), oleic acid (25 mg), and Poloxamer® 407 (0.3 g), with an entrapment efficiency of 75.2 ± 0.1%. The average size, zeta potential, and polydispersity index were determined to be 306.6 ± 49.6 nm, −10.2 ± 0.3 mV, and 0.09 ± 0.10, respectively. Moreover, an in vitro release study showed that the optimized temazepam NLC-1 formulation had a sustained release profile. Scintigraphy images showed evident improvement in brain uptake for the oral 99mTc-temazepam NLC-1 formulation versus the 99mTc-temazepam suspension. Pharmacokinetic data revealed a significant increase in the relative bioavailability of 99mTc-temazepam NLC-1 formulation (292.7%), compared to that of oral 99mTc-temazepam suspension. Besides, the NLC formulation exhibited a distinct targeting affinity to rat brain. In conclusion, our results indicate that the developed temazepam NLC formulation can be considered as a potential nanocarrier for brain-mediated drug delivery in the out-patient management of insomnia.